2015
DOI: 10.1186/s13045-015-0138-0
|View full text |Cite
|
Sign up to set email alerts
|

Deep sequencing and SNP array analyses of pediatric T-cell acute lymphoblastic leukemia reveal NOTCH1 mutations in minor subclones and a high incidence of uniparental isodisomies affecting CDKN2A

Abstract: BackgroundPediatric T-cell acute lymphoblastic leukemia (T-ALL) is a genetically heterogeneous disease that arises in a multistep fashion through acquisition of several genetic aberrations, subsequently giving rise to a malignant, clonal expansion of T-lymphoblasts. The aim of the present study was to identify additional as well as cooperative genetic events in T-ALL.MethodsA population-based pediatric T-ALL series comprising 47 cases was investigated by SNP array and deep sequencing analyses of 75 genes, in o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
31
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 49 publications
7
31
2
Order By: Relevance
“…PTEN loss‐of‐function mutations result in MYC overexpression via upregulation of the PI3K/AKT pathway and stabilized MYC protein levels . The fact that diagnostic and relapse bone marrow samples of our patient shared some PTEN deletions, while a relapse sample harbored a new mutation, also supports the hypothesis of subclone selection and may indicate relapse from the preleukemic clone . The genetic profile of our leukemia case with t(8;14)(q24;q11) and NOTCH wt / FBXW7 wt / PTEN mut agrees with that of leukemia‐initiating cells (LICs) in Pten ‐null experimental T‐ALL model.…”
Section: Discussionsupporting
confidence: 76%
“…PTEN loss‐of‐function mutations result in MYC overexpression via upregulation of the PI3K/AKT pathway and stabilized MYC protein levels . The fact that diagnostic and relapse bone marrow samples of our patient shared some PTEN deletions, while a relapse sample harbored a new mutation, also supports the hypothesis of subclone selection and may indicate relapse from the preleukemic clone . The genetic profile of our leukemia case with t(8;14)(q24;q11) and NOTCH wt / FBXW7 wt / PTEN mut agrees with that of leukemia‐initiating cells (LICs) in Pten ‐null experimental T‐ALL model.…”
Section: Discussionsupporting
confidence: 76%
“…This T cell expansion may be enhanced by IL-2 and IFN-γ which were used with DLI [16, 17]. However, even the relapse with the same Vδ5 leukemic clone, whether there was evolution in another molecule that may affect the biological behavior of a leukemic clone remains unclear, this may be identified by deep sequencing of the patient samples, which were collected at each instance of disease recurrence [1820]. …”
Section: Discussionmentioning
confidence: 99%
“…Conventional chromosome banding analyses reveal clonal abnormalities in 55–75% of T‐ALL cases (Table ), a frequency clearly lower than that of 85–90% in childhood BCP ALL (Zachariadis et al, ). However, the proportion of aberrant T‐ALL increases quite substantially if interphase fluorescence in situ hybridization (FISH) or single nucleotide polymorphism array (SNP‐A) analyses are performed (Karrman et al, ). Hence, chromosomal changes in T‐ALL often escape cytogenetic detection.…”
Section: Genetics Of T‐allmentioning
confidence: 99%
“…Whole chromosome UPIDs are very rare (<1%) in T‐ALL (Kawamata et al, ; Karrman et al, ) in contrast to pediatric BCP ALL where such UPIDs are found in 5–10% of cases (Kawamata et al, ; Lundin et al, ). One reason for this frequency discrepancy could be the fact that whole chromosome UPIDs are particularly common in aneuploid malignancies (Lundin et al, ) and that T‐ALL cases only rarely are aneuploid (Fig.…”
Section: Genetics Of T‐allmentioning
confidence: 99%